2004
DOI: 10.1007/s00417-003-0845-z
|View full text |Cite
|
Sign up to set email alerts
|

Marked reduction and distinct patterns of eye blinking in patients with moderately dry eyes during video display terminal use

Abstract: Reduction of the SEBR during VDT use is primarily determined by marked visual attention, resulting in an exacerbation of dry eye symptoms in predisposed humans. High interindividual variability and distinct patterns of eye blinking may be key factors in further clarification of VDT-eye interactions and develop individually designed solutions to prevent desiccation during VDT use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
104
2
9

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(123 citation statements)
references
References 19 publications
8
104
2
9
Order By: Relevance
“…Accordingly, the previously reported decline in blink rate when performing a task on a computer in comparison with ''general conversation'' (Patel et al, 1991;Schlote et al, 2004;Tsubota & Nakamori, 1993), cannot be attributed solely to the characteristics of the digital screen. Indeed, the magnitude of cognitive effect seen here varied for the two methods of presentation.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Accordingly, the previously reported decline in blink rate when performing a task on a computer in comparison with ''general conversation'' (Patel et al, 1991;Schlote et al, 2004;Tsubota & Nakamori, 1993), cannot be attributed solely to the characteristics of the digital screen. Indeed, the magnitude of cognitive effect seen here varied for the two methods of presentation.…”
Section: Discussionmentioning
confidence: 72%
“…One explanation for the higher prevalence of dry eye symptoms when viewing screens may be due to changes in blink patterns. Several investigations have reported that the blink rate is reduced during computer operation (Patel, Henderson, Bradley, Galloway, & Hunter, 1991;Schlote, Kadner, & Freudenthaler, 2004;Tsubota & Nakamori, 1993;Wong, Wan, & Kaye, 2002). For example, Tsubota and Nakamori (1993) compared the rate of blinking in 104 office workers either when they were relaxed, reading a book or viewing text on an electronic screen.…”
Section: Introductionmentioning
confidence: 99%
“…Spontaneous blinking rate tends to increase in patients with DED because of tear film instability 18) . On the other hand, during VDT use, the spontaneous blinking rates of both normal and DED-affected eyes decreases when compared with those at rest 19) . In our study, the high positive predictive value indicated that VDT workers who cannot keep their eyes open for 10 seconds have an increased probability of DED.…”
Section: Discussionmentioning
confidence: 88%
“…In an experimental study on 14 female clerks, Piccoli et al (1996) found a mean blink rate of 15.1 blinks per minute during VDU work, but did not record the blink rate for other situations. In a group of 30 patients with moderately dry eyes, Schlote et al (2004) found a mean blink rate of 6.6 blinks per minute during VDU work compared with 16.8 during conversation. Patel et al (1991) found a five-fold drop in the eye blink rate during VDU use.…”
Section: Article In Pressmentioning
confidence: 92%